2000
DOI: 10.1093/carcin/21.9.1737
|View full text |Cite
|
Sign up to set email alerts
|

Identification of hepatic tamoxifen–DNA adducts in mice: α-(N2-deoxyguanosinyl)tamoxifen and α-(N2-deoxyguanosinyl)tamoxifen N-oxide

Abstract: Tamoxifen-DNA adducts detected in the liver of mice treated with tamoxifen have not yet been identified. In the present study a new type of tamoxifen-DNA adduct, four stereoisomers of alpha-(N:(2)-deoxyguanosinyl)tamoxifen N:-oxide 3'-monophosphate (dG(3'P)-N:(2)-TAM N:-oxide) were prepared as standard DNA adducts by reacting 2'-deoxyguanosine 3'-monophosphate with trans-alpha-acetoxytamoxifen N:-oxide in addition to four stereoisomers of alpha-(N:(2)-deoxyguano- sinyl)tamoxifen 3'-monophosphate (dG(3'P)-N:(2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Our current study demonstrates the participation of human P450 enzymes, among these CYP3A4 in the reduction of the N-oxide of TAM. These findings and the observations that TNO forms far less DNA and protein adducts than does TAM (Dehal and Kupfer, 1999;Umemoto et al, 2000) suggest that TNO could be an attractive candidate for a prodrug of TAM. Other tamoxifen analogs undergoing clinical trials for antibreast cancer treatment (e.g., iodoxifene, toremifene, and droloxifene) have also been shown to form the corresponding N-oxides (McCague et al, 1990;John et al, 2002;Jones and Lim, 2002).…”
Section: Discussionmentioning
confidence: 80%
“…Our current study demonstrates the participation of human P450 enzymes, among these CYP3A4 in the reduction of the N-oxide of TAM. These findings and the observations that TNO forms far less DNA and protein adducts than does TAM (Dehal and Kupfer, 1999;Umemoto et al, 2000) suggest that TNO could be an attractive candidate for a prodrug of TAM. Other tamoxifen analogs undergoing clinical trials for antibreast cancer treatment (e.g., iodoxifene, toremifene, and droloxifene) have also been shown to form the corresponding N-oxides (McCague et al, 1990;John et al, 2002;Jones and Lim, 2002).…”
Section: Discussionmentioning
confidence: 80%
“…[14][15][16][17][18][19][20][21] Although N-desmethyltamoxifen, tamoxifen N-oxide, and 4-hydroxytamoxifen are major metabolites of tamoxifen, DNA adducts of these metabolites are hardly detected in the liver, 19,22) suggesting that these metabolites might be considered primarily as detoxification forms.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] α-(N 2 -Deoxyguanosinyl)tamoxifen is detected as a major DNA adduct of tamoxifen in the rat liver, and the adduct has been shown to be formed through metabolic activations, α-hydroxylation and O-sulfation, of tamoxifen. [14][15][16][17][18][19][20][21] Although N-desmethyltamoxifen, tamoxifen N-oxide, and 4-hydroxytamoxifen are major metabolites of tamoxifen, DNA adducts of these metabolites are hardly detected in the liver, 19,22) suggesting that these metabolites might be considered primarily as detoxification forms.…”
mentioning
confidence: 99%
“…Preparation of Tamoxifen-dG3′P Standards. dG3′P-N 2 -TAM, R-(N 2 -deoxyguanosinyl)-N-desmethyltamoxifen 3′-monophosphate (dG3′P-N 2 -N-desmethyl-TAM) and dG3′P-N 2 -TAM N-oxide were prepared by reacting dG3′P with R-acetoxytamoxifen, R-acetoxy-N-desmethyltamoxifen or R-acetoxytamoxifen N-oxide, as reported previously (9,(14)(15)(16) (Figure 1). The trans and cis stereoisomers of each nucleotide were isolated by HPLC.…”
Section: Tamoxifen-dna Adducts In Rats and Micementioning
confidence: 99%
“…In our previous study, two types of tamoxifen-DNA adducts, R-(N 2 -deoxyguanosinyl)tamoxifen 3′-monophosphate (dG 3′P -N 2 -TAM) 1 and R-(N 2 -deoxyguanosinyl)tamoxifen N-oxide 3′-monophosphate (dG 3′P -N 2 -TAM N-oxide) were prepared as the authentic standards. It was demonstrated that in mouse liver the epimers of trans-dG 3′P -N 2 -TAM and trans-dG 3′P -N 2 -TAM N-oxide were present as the first and the third major adducts, respectively (9). However, the second major adduct remains to be identified.…”
Section: Introductionmentioning
confidence: 98%